2015
DOI: 10.1021/acs.iecr.5b00595
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-Mediated Kraft Lignin Oxidation with Readily Available Metal Salts: What about the Effect of Ultrasound?

Abstract: The hydrogen peroxide mediated oxidative depolymerization of kraft lignin was investigated in the presence of different metal salt catalysts in acetone/water (1/1 v/v) at low temperature. Na 2 WO 4 •2H 2 O appeared to be the best catalyst, yielding four vanillin-based monomers. Using the optimized conditions, monomers were obtained in 0.51 wt % yield from lignin. This result is among the best depolymerization yield obtained from lignin using hydrogen peroxide mediated oxidation. Optimization of the reaction co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This result indicates that H 2 O 2 -induced oxidation had more obvious effects on decomposing guiacyl structures than on syringyl moiety. 17 Thus, by examining the IR spectra, we observed lignin’s three oxidation pathways in the presence of H 2 O 2 : hydroxylation, dealkylation, and oxidative coupling (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that H 2 O 2 -induced oxidation had more obvious effects on decomposing guiacyl structures than on syringyl moiety. 17 Thus, by examining the IR spectra, we observed lignin’s three oxidation pathways in the presence of H 2 O 2 : hydroxylation, dealkylation, and oxidative coupling (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Napoly et al also reported and explained the cavitation mechanism of ultrasound-driven particle size reduction of kraft lignin. 17…”
Section: Resultsmentioning
confidence: 99%
“…CoCl 2 showed the best performance among the investigated catalysts with a maximum yield of 6.3 wt % (vanillin and methyl vanillate) at 170 °C and 1.0 MPa O 2 ( Table 1 , Entry 13). In addition, the H 2 O 2 mediated oxidative solvolysis of kraft lignin was also investigated in the presence of different metal salt catalysts (Fe 2 (SO 4 ) 3 , Fe(NO 3 )·9H 2 O, Mn(SO 4 )·H 2 O, Bi 2 (SO 4 ) 3 , Bi(NO 3 ) 3 ·5H 2 O, H 2 WO 4 , and Na 2 WO 4 ·2H 2 O) in acetone/water with the use of ultrasound irradiation [ 71 ]. The Na 2 WO 4 ·2H 2 O catalyst was the most efficient regarding the total yield of vanillin-based monomers (vanillin, acetovanillone, vanillic acid, and guaiacol) with a maximum yield of 0.51 wt % at 45 °C ( Table 1 , Entry 14).…”
Section: Oxidative Solvolysis Of Ligninmentioning
confidence: 99%
“…This means that in most cases, acidic extraction leads to a larger extent of depolymerization reaction (Table 1 ; Entry 3) [ 66 ]. Additionally, work by Napoly and co-workers shows that it is possible to obtain vanillin-based monomers with yield equal to 0.51 wt% in the presence of a tungsten-based catalyst and an oxidizing agent such as H 2 O 2 [ 67 ]. Na 2 WO 4 acted as the most promising catalyst, which promoted an effective system, where ultrasound generated sufficient oxidation conditions (20 kHz, 11 W) and involved strengthened oxidative coupling of phenoxy radicals [ 67 ].…”
Section: Ultrasound-assisted Catalysis For Lignocellulosic Biomass Vamentioning
confidence: 99%